B(Ml) and (I1 II f - Al-Alawy, I.T.; lbraheim, K. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In the present work the nuclear structure of even-even Ba(A=130-136, Z=56) isotopes was studied using (IBM-1). The reduced matrix element of magnetic dipole moment (11 II f(Ml) II/,) and the magnetic dipole transitions probability B(M 1) were calculated for one and two bodies of even-even Ba(A=lJ0-136, Z=56). A good agreement had been found of present with available experimental data.